Mental Health Literacy about Personality Disorders: A Multicultural Study - Kerim Alp Altuncu; Arianna Schiano Lomoriello; Gabriele Lo Buglio; Ludovica Martino; Asrin Yenihayat; Maria Teresa Belfiore; Tommaso Boldrini (Behavioral Sciences, 2023)
Mental health literacy (MHL) refers to lay people’s knowledge and beliefs about the diagnosis and treatment of mental illness. The current study aimed at investigating MHL regarding personality disorders (PDs) multiculturally, comparing Turkish and Italian populations. In total, 262 participants responded to an online vignette identification task that required them to label the PDs of seven hypothetical subjects and rate various dimensions of their disorders. Narcissistic (25%), obsessive-compulsive (13%), and paranoid (12%) PDs were the most correctly labeled, while the average accuracy values for other PDs were below 0.04%. Compared to Turkish participants, Italian participants were more accurate in labeling narcissistic PD. Additionally, of the seven PDs, narcissistic PD was associated with the most happiness and success at work. Subjects with borderline and avoidant PDs were the most recognized as having psychological problems (>90%), yet their PDs were among the least correctly identified. Overall, participants from both cultures were generally successful at recognizing the presence of a mental illness, but they rarely labeled it correctly. Only limited cultural differences emerged. The present findings may inform the design of outreach programs to promote MHL regarding PDs, thereby facilitating early recognition of PDs and help-seeking behaviors for affected individuals.